Peran Guru Pendidikan Agama Islam dalam Menumbuhkan Sikap Toleransi Beragama di Kalangan Siswa SMKN 1 Palabuhanratu: Sebuah Pendekatan Inklusif - Mu'min, U Abdullah; Andesta, Nesvia; Rahmawati, Ayi (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
This study aims to examine the role of Islamic Religious Education (PAI) teachers in fostering religious tolerance among students at SMKN 1 Palabuhanratu. In the context of Indonesia's multicultural and multireligious society, the role of PAI teachers is crucial in instilling the values of moderate Islam (wasathiyah), which emphasizes respect for diversity. This study employs a descriptive qualitative approach using data collection techniques such as observation, documentation, and in-depth interviews with three Islamic Religious Education (PAI) teachers and ten students. The findings reveal that PAI teachers perform four main roles: as demonstrators, classroom managers, facilitators, and mediators. They serve as role models in tolerant behavior, create inclusive classroom environments, facilitate interfaith discussions, and address potential conflicts through dialogic and solution-oriented approaches. The teaching practices implemented include group discussions, case studies, interfaith activities, and the use of contextual learning media related to diversity issues. Teachers also collaborate with parents and interfaith leaders to extend the reach of character education promoting tolerance beyond the school setting. These findings affirm that religious education grounded in universal human values can serve as an effective instrument in shaping open-minded individuals able to live harmoniously in a pluralistic society. Therefore, strengthening the competencies of PAI teachers and adopting multicultural approaches in education are key to fostering social cohesion and peace amid Indonesia's diversity.